Independent and joint association of accelerometer-measured sedentary behaviour and physical activity with mild cognitive impairment and intrinsic capacity decline among Chinese older adults: study protocol for a cross-sectional study - Qing Zhao; Shuo Luan; Qizhi Wu; Ruoxi Lai (BMJ Open)
Introduction Numerous studies have indicated that sedentary behaviour (SB) negatively impacts cognitive function, while engaging in physical activity (PA) helps maintain cognitive performance and delay cognitive decline. However, fewer studies have examined the interaction between these two factors on cognitive function, especially among the Chinese older population. In the realm of healthy and active ageing, intrinsic capacity emerges as another crucial determinant for maintaining functional wellness. However, the independent and joint relationship of SB and PA to intrinsic capacity remains unknown. Given the substantial implications of cognitive function and intrinsic capacity decline, this study will be the first to investigate the independent and joint association of SB and PA with cognition and intrinsic capacity in Chinese older adults.Methods and analysis This is a single-centre, cross-sectional, observational and exploratory study design targeting the older population from communities in Beijing. Our study population will include 270 older individuals aged 65 years and above. SB and PA levels will be tracked using triaxial accelerometers (GT3X+, ActiGraph, Pensacola, FL, USA), worn on the dominant-side waist by participants for seven consecutive days. A well-designed questionnaire will be used to gather initial data on the sociodemographic and other characteristics (all relevant risk factors for mild cognitive impairment (MCI) and intrinsic capacity decline). These characteristics will later be included as confounders in multivariate regression analyses. Participants will be screened for MCI using the montreal cognitive assessment scale, the clinical dementia rating scale and the activities of daily living scale. The amnestic MCI subtype will undergo additional evaluation using the mini-mental state examination scale and the MemTrax continuous memory recognition test. The integrated care for older people screening tool will evaluate the intrinsic capacity of older adults. To further investigate the interaction between SB and PA, participants will be divided into the following groups: (1) Mildly sedentary+active, (2) Mildly sedentary+inactive, (3) Severely sedentary+active and (4) Severely sedentary+inactive. 270 older participants will be stratified by age: 65–69 years, 70–79 years and ≥80 years. We will compare the prevalence of MCI and amnestic MCI, as well as intrinsic capacity scores, among older adults with different levels of SB and PA across these three age groups, and calculate ORs and 95% CIs.Ethics and dissemination Approval for the project was granted by the Sports Science Experiment Ethics Committee of Beijing Sport University on 12 June 2024 (ID: 2024193H). Participants will provide informed consent, guaranteeing voluntary participation. The data collected will be anonymised and securely stored in a database. The results of the study will be disseminated through open-access, peer-reviewed publications and scientific events.Trial registration number ChiCTR2400085482.